The Influence of Teacher Interpersonal Communication on Students' Interest in Learning (Case Study of Students at the Private Madrasah Aliyah Plus Al-Ullum School) - Nandini; Sallima Zarli Lubis; Vira Nabila Hadori; Maulana Adinata Dalimunthe (Penerbit Hellow Pustaka, 2024)
In the teaching and learning process there must be good communication applied by the teacher to the students. So, the learning process will run well and students can feel comfortable, not bored, willing to pay close attention to learning, a close relationship between students and teachers, the boring learning and teaching process is the help of a teacher, learning that Monotony will make it difficult for students to pay close attention to the discussion that has been explained by the teacher. Good interpersonal communication will support enthusiasm for learning and increase students' interest in learning at the private MAS plus Al-ulum. Good communication can also make students themselves comfortable and not prejudiced against the teacher's response.